2009
DOI: 10.1093/ndt/gfp599
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin and high glucose promote renal tubular inflammation

Abstract: In conclusion, HG stimulates tubular proinflammatory, profibrotic and angiogenic signals, which is partly mediated through BK via MAPK signalling and partly through PKC independent of BK. The potential therapeutic role of complementary B(2)KR blockade and PPAR-gamma activation deserves clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 41 publications
5
69
0
Order By: Relevance
“…Indeed, participation of the KKS in DN has become increasingly apparent. We recently observed expression of kallikrein in the proximal tubules of human diabetic kidney tissue, 3 whereas Campell et al 8 reported increased plasma levels of tissue kallikrein in type 2 diabetic subjects. However, there are conflicting in vitro and animal data, as to whether KKS overactivation is good (protective) or bad (destructive) in DN.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Indeed, participation of the KKS in DN has become increasingly apparent. We recently observed expression of kallikrein in the proximal tubules of human diabetic kidney tissue, 3 whereas Campell et al 8 reported increased plasma levels of tissue kallikrein in type 2 diabetic subjects. However, there are conflicting in vitro and animal data, as to whether KKS overactivation is good (protective) or bad (destructive) in DN.…”
Section: Discussionmentioning
confidence: 83%
“…As we recently demonstrated upregulation of CCL2 and TGF-b in cultured proximal tubular cells to HG, 3 we next performed immunohistochemical staining to localize these two cytokines in mouse kidney sections. Both CCL2 (proinflammatory) and TGF-b (profibrotic) were present in renal proximal tubules of db/db mice ( Figure 6) and the staining intensity after various treatments mirrored those of the western blots as described above.…”
Section: Interstitial Fibrosismentioning
confidence: 99%
See 3 more Smart Citations